Signature of magnetization in Xe ions implanted ZnO : correlation with oxygen defects as probed by photoelectron spectroscopy - Chatterjee, Ratnamala (2019)
300 keV Xe ions were implanted in single crystals of ZnO at room temperature with three fluences viz. 4.9 × 1015, 8.1 × 1015 and 1.1 × 1016 ions/cm2. The Xe ion implanted ZnO samples were characterized by UV-Vis spectroscopy, X-ray photo-electron spectroscopy (XPS) and SQUID magnetometer. It has been noticed that the samples implanted with lowest and highest ion fluences show magnetization higher than that in the sample implanted with intermediate ion fluence. This unusual trend in the change of the magnetization is attributed to the lattice distortion and the variation in the lattice oxygen concentration as evidenced from the core level XPS results. The results are explained in terms of oxygen vacancies mediated bound magnetic polarons (BMP) and ion induced effects on their formation.